Nilai Islam Dalam Media (Analisis Wacana Kritis Film Hati Suhita) - Fitria, Ninis; Rio Febriannur Rachman (LPPM Stikosa - AWS, 2024)
This study discusses the Islamic values contained on the media in the form of the film Hati Suhita. with a relatively large audience of 507,167 in 2023. The aim of this study is to reveal the da'wah discourse and the Islamic values contained in the film. There are a number of theories used, including the da'wah theories popularized by Ansari and Asmuni Syukur. The theories discuss